Informatização do setor de fitotecnia: estudo de caso da Fundação ABC - Iaros, Angelica (2013)
ABC Foundation is a non-profit organization, mantained by three other companies that work with research and development of technologies on the agricultural field. The Crop Science sector of the company needed a computerized tool to help with the data collection performed by the department. This tool was developed for the Web, employing resources such as the JQuery Handsontable library, the SCRUM methodology, SQLite manager database and RIA concepts. The company considered the results coming out from the tool as satisfatory, once the tool was able to fulfill the task of providing all the gathered information on the field in real time, making easier, in this way, the conclusion of the performed activities by the employees of the department.